Infiltrasi Dakwah Moderat dalam Novel Kyai Joksin - Kyai Tanpa Pesantren - Nuriyah Nuriyah (Religia, 2018)
This article aims to explain dakwah in the fiction novel Kyai Joksin Kyai Tanpa Pesantren by Imam Sibawaih el-Hasany. A literary work more often than not contains messages the author wants to convey. Religious moral messages are often presented in the form of a novel, with the goal of inspiring the readers. Novel Kyai Joksin Kyai Tanpa Pesantren is one of the literary works full of religious messages, which are particularly connected to dakwah. Through the lens of dakwah theory, this study focuses on the method of dakwah used by Kyai Joksin. This study concludes that Novel Kyai Joksin Kyai Tanpa Pesantren is a narrative about the journey of a kyai who has no pesantren (English: Islamic boarding school). Despite this drawback, but the preaching of the kai turns out to be effective. This effectiveness resides upon the methods of the dakwah the kyai applied which are characterised by politeness and gentleness, uswatun hasanah, advice, wills, wisdom, justice, and dialogue.